2020
DOI: 10.1016/j.immuni.2020.06.022
|View full text |Cite
|
Sign up to set email alerts
|

The Cytokine IL-17A Limits Th17 Pathogenicity via a Negative Feedback Loop Driven by Autocrine Induction of IL-24

Abstract: Summary Dysregulated Th17 cell responses underlie multiple inflammatory and autoimmune diseases, including autoimmune uveitis and its animal model, EAU. However, clinical trials targeting IL-17A in uveitis were not successful. Here, we report that Th17 cells were regulated by their own signature cytokine, IL-17A. Loss of IL-17A in autopathogenic Th17 cells did not reduce their pathogenicity and instead elevated their expression of the Th17 cytokines GM-CSF and IL-17F. Mechanistic in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(125 citation statements)
references
References 59 publications
7
117
1
Order By: Relevance
“…Because anti-IL-17A treatment results in increased Bph titers, this worsened infection may offset the effects of IL-17A blockade by further stimulating a bacterial Th17 immune response, which is consistent with our observation that Th17 cells were not reduced in colonized mice treated with anti-IL-17A ( Figure 4I ). Alternatively, recent advances have shown that blocking IL-17A may lead to a compensatory upregulation of other Th17-related cytokines in some types of Th17 cells, which could also mitigate the effects of anti-IL-17A antibodies ( Chong et al, 2020 ). Together, our data support previously described protective roles for Th17 in blunting allergic effector responses ( Schnyder-Candrian et al, 2006 ) but additionally implicate immune responses to airway commensals as a potential source for this Th17 response.…”
Section: Discussionmentioning
confidence: 99%
“…Because anti-IL-17A treatment results in increased Bph titers, this worsened infection may offset the effects of IL-17A blockade by further stimulating a bacterial Th17 immune response, which is consistent with our observation that Th17 cells were not reduced in colonized mice treated with anti-IL-17A ( Figure 4I ). Alternatively, recent advances have shown that blocking IL-17A may lead to a compensatory upregulation of other Th17-related cytokines in some types of Th17 cells, which could also mitigate the effects of anti-IL-17A antibodies ( Chong et al, 2020 ). Together, our data support previously described protective roles for Th17 in blunting allergic effector responses ( Schnyder-Candrian et al, 2006 ) but additionally implicate immune responses to airway commensals as a potential source for this Th17 response.…”
Section: Discussionmentioning
confidence: 99%
“…In the skin, fungal recognition by PRR on myeloid cells (DC, macrophages, neutrophils) and, probably, keratinocytes and fibroblasts trigger the production of cytokines like IL-23, IL-6, IL-1β, and IL-21 ( 51 , 53 , 90 ). Cytokine binding to its receptor on lymphocytes selectively triggers intracellular Signal Transducer and Activator of Transcription 3 (STAT3) phosphorylation, Retinoic-acid-receptor-related orphan nuclear receptor gamma (RORγt) transcription factor activation and, eventually, leads to the induction of Th17 lineage or the synthesis of type 17-cytokines (IL-17, GM-CSF, IL-22) ( 92 ). Noteworthily, IL-17A can also activate STAT3 in keratinocytes and amplify IL-6 production ( 80 ) ( Figure 2 ).…”
Section: Type 17 (Il-17-mediated) Immunity In Dermatophytosismentioning
confidence: 99%
“…IL-17A upregulated IL-24 expression in normal human keratinocytes [15,36]. Chong et al [37] found that IL-17A induced IL-24 production in Th17 cells. Considering that IL-17A signals through the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway [38] and two potential NF-κB binding sites are present in the IL-24 gene, the researchers proposed that the binding of IL-17A to its receptor activates NF-κB signaling, leading to the transcription of IL-24 in Th17 cells [37].…”
Section: Cytokines Il-17a Il-22 and Il-23mentioning
confidence: 99%